2022
DOI: 10.1186/s12888-022-03739-z
|View full text |Cite
|
Sign up to set email alerts
|

Prevalence and biopsychosocial factors associated with depressive symptoms among patients living with systemic lupus erythematosus in clinical settings in urban Thailand

Abstract: Background Depressive symptoms are globally recognized as a significant mental health problem in patients with chronic disease, particularly those with systemic lupus erythematosus (SLE). The purpose of this study was to estimate the prevalence and examine biopsychosocial factors of depressive symptoms among patients with SLE. Methods This cross-sectional study was conducted among 185 participants diagnosed with SLE and received treatment for at le… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

3
5
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(9 citation statements)
references
References 74 publications
3
5
0
Order By: Relevance
“…We found paid employment status to be protective against both anxiety and depression with corresponding odds ratios of 0.18 and 0.23, independent of SLE severity measures such as SLEDAI and organ damage. This is in agreement with other studies that have identified socioeconomic factors, in particular unemployment, financial strain, or low-social support, as significant correlates of depression in SLE [ 5 , 14 , 19 , 23 , 61 ]. Indeed, mediation modeling has suggested that low-socioeconomic status may impact negatively on the psychosocial resilience [ 61 ] and perceived stress [ 13 ] of lupus patients, thus contributing to higher anxiety, depression, and subsequent disability.…”
Section: Discussionsupporting
confidence: 93%
See 3 more Smart Citations
“…We found paid employment status to be protective against both anxiety and depression with corresponding odds ratios of 0.18 and 0.23, independent of SLE severity measures such as SLEDAI and organ damage. This is in agreement with other studies that have identified socioeconomic factors, in particular unemployment, financial strain, or low-social support, as significant correlates of depression in SLE [ 5 , 14 , 19 , 23 , 61 ]. Indeed, mediation modeling has suggested that low-socioeconomic status may impact negatively on the psychosocial resilience [ 61 ] and perceived stress [ 13 ] of lupus patients, thus contributing to higher anxiety, depression, and subsequent disability.…”
Section: Discussionsupporting
confidence: 93%
“…In our sample comprising of active SLE patients with an average age and disease duration of 50.5 and 10.3 years, respectively, significant anxiety (HADS-A ≥ 11) and depression (HADS-D ≥ 8) was each noted in 52.5%. This is in line with the results from previous cross-sectional observational studies [ 7 , 11 , 18 , 23 , 50 , 51 , 52 , 53 ] and meta-analyses of published data [ 3 , 4 ], although reported rates may vary according to the study design, population characteristics, and diagnostic instruments used. In the same context, a large Danish cohort study found that compared with the general population, the adjusted hazard ratio of depression was 2.22 (95% CI 1.77–2.77) for SLE patients [ 54 ].…”
Section: Discussionsupporting
confidence: 90%
See 2 more Smart Citations
“…1,2 Particularly, pain, fatigue, dissatisfaction with body image and poor social support are strongly associated with depressive symptoms in patients with SLE. 3 Unfortunately, not all disease-related factors that impair HRQoL can be directly addressed with better SLE treatment, since pharmacotherapy cannot reverse disease-related organ damage nor directly improve fatigue or body image. Therefore, there is a need to comprehensively study HRQoL in SLE in order to improve patient care via strategic and possibly non-pharmacologic interventions.…”
Section: Introductionmentioning
confidence: 99%